1967
DOI: 10.1002/j.1537-2197.1967.tb06923.x
|View full text |Cite
|
Sign up to set email alerts
|

Niacin Biosynthesis in Germinating×laeliocattleya Orchid Embryos and Young Seedlings

Abstract: The roles of tryptophan, kynurenne, 3‐hydroxyanthranilic acid, and quinolinic acid as niacin precursors were investigated by assessing their germination and growth‐promoting effects in orchid embryo and seedling cultures. Only niacin, 3‐hydroxyanthranilic acid, quinolinic acid and kynurenine exhibited a growth‐promoting effect on seedlings of all ages. Tryptophan inhibited the growth of 70‐day‐old seedlings but enhanced growth of older seedlings. The data presented are interpreted to be consistent with the hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1969
1969
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Peptone was also responsible for increased uniformity of seedling development. Niacin has also been found to be beneficial for orchid seed germination (Arditti, 1967). Niacin and its derivatives are essential for metabolism as components of NAD + and NADP + .…”
Section: Discussionmentioning
confidence: 99%
“…Peptone was also responsible for increased uniformity of seedling development. Niacin has also been found to be beneficial for orchid seed germination (Arditti, 1967). Niacin and its derivatives are essential for metabolism as components of NAD + and NADP + .…”
Section: Discussionmentioning
confidence: 99%
“…3.2.3. Effect of Jrhs Proliferation on Media Containing Proteins, Amino Acids, B Vitamins, and Plant Growth Regulators Nitrogen or amino acids brought many benefits to growth or morphogenesis, including increased callus formation, prevention of browning, and increased protocorm-like bodies, seedlings and the yield of orchids [17,[42][43][44].…”
Section: Effect Of Ba and Iaa Concentrations On The Proliferation Of ...mentioning
confidence: 99%
“…Jrhs that cultured with 1 g/L tryptone obtained significantly (p < 0.05) larger size and better proliferation rate, which were 8.9 ± 2.0 mm and 12.4, respectively. Tryptone is mainly composed of amino acids and vitamins [42]. Related research data showed that 2 g/L tryptone in the culture medium could help the development of Paphiopedilum primulinum and Phaius tankervilliae seeds [29,45] as well.…”
Section: Effect Of Ba and Iaa Concentrations On The Proliferation Of ...mentioning
confidence: 99%
“…Development was measured by the growth index method (fig. l;SPOl~RL 1948;ARDITTI 1967b). A total of400 seedlings (100 seedlings per replica) were evaluated for each medium.…”
Section: Introductionmentioning
confidence: 99%